Korelasi antara Penggunaan Alat Permainan Edukatif terhadap Perkembangan Kognitif Anak di RA. Nurul Huda Kraton Pasuruan - Nur Hasanah; M. Mujib Utsmani (LP3M STITNU AL HIKMAH MOJOKERTO, 2022)
This study raised the correlation of educationalgames on children’s cognitive development base on observation of reserchs at RA. Nurul Huda palace, the existence of APE has not been used optimally in the learning process even thought its existence is very important to stimulate every aspect of child development, especially cognitive development.The condition of APE, knowing the cognitive development of children and knowing how much influence APE has on children’s development. This study uses quantitative research methods with the type of research is experimental research. This research uses a reaserch design pre-experimental design with one-group pre-test-post-test design. This method is used because this studyaims to determine the correlation between the use of APE to children’s cognitive development before and after being given the following treatment the research chart according to arikunto ( 2006 : 85) As for subject in this study were 20 children of group B in RA Nurul huda kraton pasuruan, the data collection technique used the observation , interview, question/ questioner and documentation after the data analysis process was carried out so that the score increased between pre test and post test. That is the score mean rank or an average of 17.00 while the sum of rank or the number of positive rank of 340,00 based on the result of the above analysis, the researchers concluded that there was a significant correlation between the use of APE in children’s cognitive development .